2019
DOI: 10.1002/ls.1453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of base oil polarity on the micropitting behaviour in rolling‐sliding contacts

Abstract: An automated micropitting test rig that uses the proven three‐point contact configuration was applied to study the effect of base oil polarity on micropitting behaviour in rolling‐sliding contacts. The tribological tests using one polar (ester) and one non‐polar (polyalpha olefin [PAO]) base oil mixed with four different additives were first done in a micropitting rig to study the friction, wear, and micropitting performance. The tested specimen after tribological tests were examined by an optical microscope t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
(78 reference statements)
3
2
0
Order By: Relevance
“…Our ToF-SIMS data shows PAO surface to be covered by relatively higher concentration of long chain metaphosphates than in ester oil. The results are in agreement with Cen et al [55] who found phosphate chain length of ZDDP tribo lm to be longer in PAO than in ester based oil. It is also known that short chain phosphates and consequent nanocrystallization generally contributes to a resilient tribo lm than reaction layers formed of longer chains [50].…”
Section: 4supporting
confidence: 93%
See 2 more Smart Citations
“…Our ToF-SIMS data shows PAO surface to be covered by relatively higher concentration of long chain metaphosphates than in ester oil. The results are in agreement with Cen et al [55] who found phosphate chain length of ZDDP tribo lm to be longer in PAO than in ester based oil. It is also known that short chain phosphates and consequent nanocrystallization generally contributes to a resilient tribo lm than reaction layers formed of longer chains [50].…”
Section: 4supporting
confidence: 93%
“…It is also known that short chain phosphates and consequent nanocrystallization generally contributes to a resilient tribo lm than reaction layers formed of longer chains [50]. Further, the tribo lms formed by short chain phosphates are shown to be harder than those formed by the overlying long chain phosphates [55,62]. With increase in hardness there can be a decrease in both the adhesive and deformation components of the measured friction coe cient [63].…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the P 2p spectra of the ZnTCPP/ LSMO/STO only had one peak centered at 140 eV, which corresponds to Zn 3s. 43,44 The above results confirmed the successful formation of ZnTCPP and ZnTCPP−DNA films. Figure 1e,f show the measured I−V curves of the ZnTCPPand ZnTCPP−DNA-based devices, respectively, for 50 cycles of the 0 → 3 → 0 → − 3 → 0 V DC voltage sweep mode.…”
Section: Resultssupporting
confidence: 72%
“…These can be attributed to P 2p 3/2 in PO 4 3– of the DNA backbone, P 2p 1/2 in the phosphorus of sodium phosphate, and Zn 3s in ZnTCPP, respectively. In contrast, the P 2p spectra of the ZnTCPP/LSMO/STO only had one peak centered at 140 eV, which corresponds to Zn 3s. , The above results confirmed the successful formation of ZnTCPP and ZnTCPP–DNA films.…”
Section: Resultssupporting
confidence: 66%